Optimalisasi Peningkatan Kompetensi Orang Tua Dalam Pendampingan Belajar Anak Melalui Parenting Learning Style Strategy - Nuhyal Ulia; Rida Fironika Kusumadewi; Mohamad Haryono; Devi Suci Rahmawati (Pusmedia Group Indonesia, 2026)
Parental guidance plays a crucial role in helping students understand the material presented at school and in completing their assignments. However, parents often fail to understand their child's preferred learning style. They may even be unaware of whether their child is an auditory, visual, or kinesthetic learner. Consequently, the guidance provided to children is suboptimal, impacting student learning outcomes. Current learning styles, which increasingly facilitate students' learning styles in schools, have not been matched by parental guidance that aligns with their child's learning style. Based on this background, the purpose of this community service activity is to educate parents about learning style strategies, identify their child's preferred learning style, and improve student learning outcomes after receiving parental guidance through the Learning Style Strategy. The purpose of this community service activity is to increase parents' understanding of learning styles and to improve students' learning outcomes using the Learning Style Strategy. The community service method used is Participatory Action Research, which consists of five stages: initial socialization, social mapping, participatory planning, action implementation, and monitoring and evaluation. The results of the community service activities obtained the results of mapping student learning styles at kinesthetic by 23%, audio 37% and visual 40%. In addition, there was an increase in parental competence measured from before and after the community service activities by 84%, including in the high category. Increased parental competence affects learning assistance to their children and influences student learning outcomes.